Engineered biosynthesis of plant polyketides by type III polyketide synthases in microorganisms - Liu, Chang; Li, Sijin (Frontiers in Bioengineering and Biotechnology, 2022)
Plant specialized metabolites occupy unique therapeutic niches in human medicine. A large family of plant specialized metabolites, namely plant polyketides, exhibit diverse and remarkable pharmaceutical properties and thereby great biomanufacturing potential. A growing body of studies has focused on plant polyketide synthesis using plant type III polyketide synthases (PKSs), such as flavonoids, stilbenes, benzalacetones, curcuminoids, chromones, acridones, xanthones, and pyrones. Microbial expression of plant type III PKSs and related biosynthetic pathways in workhorse microorganisms, such as Saccharomyces cerevisiae, Escherichia coli, and Yarrowia lipolytica, have led to the complete biosynthesis of multiple plant polyketides, such as flavonoids and stilbenes, from simple carbohydrates using different metabolic engineering approaches. Additionally, advanced biosynthesis techniques led to the biosynthesis of novel and complex plant polyketides synthesized by diversified type III PKSs. This review will summarize efforts in the past ten years in type III PKS-catalyzed natural product biosynthesis in microorganisms, especially the complete biosynthesis strategies and achievements.